Exploring the Determinants of Repurchase Intention and Word of Mouth Intention in Social Commerce - Warniancy Ariesty; Ridho Bramulya Ikhsan (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose – This study aims to analyze the factors that affect customer intention to make a repeat purchase and provide recommendations to others on social commerce platforms.Methodology – This study uses a quantitative study design with data collection through online surveys. The respondents from this study were 220 respondents who actively used social commerce platforms and had made purchases on social commerce platforms. The research model was tested using SmartPLS software version 4.Findings – Based on the research results, it can be concluded that Reputation has a positive effect on Satisfaction, Information Quality has a positive effect on Satisfaction, Transaction Safety has a positive effect on Satisfaction, Satisfaction has a positive effect on Repurchase Intention, and Satisfaction has a positive effect on WOM Intention.Originality/Novelty – This study's novelty lies in adding transaction safety variables directly related to consumer satisfaction.Implications – Maintaining and improving reputation is very important, and businesses need to consistently build a positive image and credibility in the eyes of consumers. To ensure a strong reputation, focus on transparency, integrity, and quality of service. To increase transparency, social commerce businesses must ensure that the information provided is clear, timely, and useful for consumers. In addition, transaction security is also a top priority to create satisfaction that can encourage repurchase intentions and WOM from consumers.